If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3h + -7 = 1 Reorder the terms: -7 + 3h = 1 Solving -7 + 3h = 1 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 3h = 1 + 7 Combine like terms: -7 + 7 = 0 0 + 3h = 1 + 7 3h = 1 + 7 Combine like terms: 1 + 7 = 8 3h = 8 Divide each side by '3'. h = 2.666666667 Simplifying h = 2.666666667
| 5x=-2x+8+8 | | 9+5=711 | | 2z/7-5=8 | | 1/2x-5=3/4Xx-5=3/4x | | -2.6=-3.3-x | | 6x+13=-55-3x | | 4/5c-16=8 | | 8x-71=4x-11 | | 4x+16y=6 | | X-15=5.25 | | 5b-0.7=66 | | 3(x+1)-2=8x+20-8 | | z/10-8=4 | | u^2-16u+3=0 | | b-5+7=26 | | -9=-2r+8 | | 8p-2(p-1)=2(3p-1) | | s=4p | | Priyanshux=4 | | 10x-70=6x-30 | | 2,41x-4,9=6,7 | | 6/0.009 | | Cosx=4 | | -122+X=-4.55 | | 4x+2y=9.5 | | 15=p/3-12 | | 2x^2/3=8 | | 5m/3-3=m/6 | | 10x^2+90x+14=0 | | 2the+2priyanshu=2priyanshu-2the | | 5x-10+3x+2= | | 9d+2d+3d-4=rd |